ANALISIS WACANA BODY SHAMING DALAM FILM IMPERFECT (STUDI ANALISIS WACANA TEUN A. VAN DIJK) - Nugraha, Putri Larasati; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2021)
Imperfect film features body shaming as the main focus of the story as well as depicting the impact felt by victims due to continuous body shaming. This research was conducted to find out the discourse displayed by Ernest Prakasa as director in the film